ANALYSIS OF FAMILY PROSPERITY AND INCOME CONTRIBUTION OF FISHERMAN’S WIVES AT CILACAP VILLAGE, CILACAP - Azis Nur Bambang (JOURNAL OF COASTAL DEVELOPMENT, 2005)
The objective of this research is to know level of family prosperity and income of fisherman’s wives andto know amount of income contribution of fisherman’s wives in Cilacap. Case study method was used inthis research. Result of research indicates that level of family prosperity of labor fisherman’s wives withERF = 1,26 is lower compared to level of family prosperity of entrepreneur fisherman’s wives (ERF =1,47). Income of labor fisherman’s wives Rp.292 000 is lower compared to income of entrepreneurfisherman’s wives (Rp 742 500). Income contribution of labor fisherman’s wives is 39,22 %, whileincome contribution of entrepreneur fisherman’s wives is 46,05 %.